GISimos MCDA land suitability model for ecotourism development - Aşılıoğlu, Fatma (Journal of Environmental Engineering and Landscape Management, 2021)
Ecotourism development planning is a multi-criteria process that generally requires spatial analysis. GISimos MCDA model developed by this study, was presented for the first time and applied to the Kalecik sub-province of Ankara, Turkey to determine the suitable areas and their suitability levels for ecotourism development. The model is based on the evaluation of sub-factors representing the topography, land cover, climate and sociocultural characteristics of the region, with the combination of GIS and the revised Simos procedure, one of the MCDA techniques. It included a series of processes such as determining the suitability rates and weights of sub-factors, calculating the Ecotourism Suitability Index values, and overlapping them using the WLC method. The resulting values were categorized as highly suitable, moderately suitable, marginally suitable, and not suitable areas. The results of this study and the method developed will be helpful for decision-makers and planners in the study area and similar regions.